Tsunami-generated magnetic fields have primary and secondary arrivals like seismic waves - Takuto Minami (Nature Portfolio, 2021)
Abstract A seafloor geomagnetic observatory in the northwest Pacific has provided very long vector geomagnetic time-series. It was found that the time-series include significant magnetic signals generated by a few giant tsunami events including the 2011 Tohoku Tsunami. Here we report that the tsunami-generated magnetic fields consist of the weak but first arriving field, and the strong but second arriving field—similar to the P- and S-waves in seismology. The latter field is a result of coupling between horizontal particle motions of the conductive seawater and the vertical component of the background geomagnetic main field, which have been studied well so far. On the other hand, the former field stems from coupling between vertical particle motions and the horizontal component of the geomagnetic main field parallel to tsunami propagation direction. The former field has been paid less attention because horizontal particle motions are dominant in the Earth’s oceans. It, however, was shown that not only the latter but also the former field is significant especially around the magnetic equator where the vertical component of the background magnetic field vanishes. This implies that global tsunami early warning using tsunami-generated magnetic fields is possible even in the absence of the background vertical geomagnetic component.